Optimalisasi Berpikir Historis Melalui Program Pengenalan Lapangan Persekolahan di SMAN 1 Baros untuk Meningkatkan Pemahaman Siswa Terhadap Pembelajaran Sejarah - Kamelia Putri; Fajar Sucipto; Santi Dame Mawarni; Ahmad Hiisyam Syauqi Solihin; Dian Rachmawati; Cicih Sairoh (Universitas Palan, 2025)
This study aims to optimize students' historical thinking skills through the School Environment Introduction Program at SMAN 1 Baros. This program is designed to improve students' understanding of history by developing critical, analytical, and interpretive skills in understanding historical events. The research methods used are literature studies and case studies. The results of the study indicate that students' historical thinking skills at SMAN 1 Baros are still low, which is caused by lecture-based learning and limited learning resources. This program focuses on developing an understanding of the concepts of time, space, and society, as well as the application of interactive and project-based learning to improve students' critical thinking skills. This optimization is expected to create a generation that thinks independently, creatively, and wisely in facing global and local challenges.